Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-23642-7
|View full text |Cite
|
Sign up to set email alerts
|

A functional motif of long noncoding RNA Nron against osteoporosis

Abstract: Long noncoding RNAs are widely implicated in diverse disease processes. Nonetheless, their regulatory roles in bone resorption are undefined. Here, we identify lncRNA Nron as a critical suppressor of bone resorption. We demonstrate that osteoclastic Nron knockout mice exhibit an osteopenia phenotype with elevated bone resorption activity. Conversely, osteoclastic Nron transgenic mice exhibit lower bone resorption and higher bone mass. Furthermore, the pharmacological overexpression of Nron inhibits bone resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…lncRNAs can also easily be synthesized and delivered using chemically modified lipid nanoparticles or exosomes to improve RNA stability and increase tissue specificity. Recent advances have identified short, functionally active fragments of lncRNAs (“lncRNA mimics”), which mimic the effect of the full-length lncRNA ( 91 , 92 ). These fragments might have reduced immunogenicity and can potentially be modified to increase in vivo stability and tagged with organ-targeting peptides to improve tissue specificity.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs can also easily be synthesized and delivered using chemically modified lipid nanoparticles or exosomes to improve RNA stability and increase tissue specificity. Recent advances have identified short, functionally active fragments of lncRNAs (“lncRNA mimics”), which mimic the effect of the full-length lncRNA ( 91 , 92 ). These fragments might have reduced immunogenicity and can potentially be modified to increase in vivo stability and tagged with organ-targeting peptides to improve tissue specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the development of multiple RNA detection techniques ( Shu et al, 2021 ; Toden et al, 2021 ; Wang et al, 2021 ; Zhong et al, 2021a ), most RNAs have been found to lack the capacity to encode proteins. Although these RNAs do not directly translate into proteins ( Gupta et al, 2020 ), driving evidence clarifies that they play an essential role in biological functions ( Chen et al, 2020b ; Jantrapirom et al, 2021 ; Jin et al, 2021 ; Lai et al, 2021 ; Zhang et al, 2021b ). Such is the case of long non-coding RNAs (lncRNAs), which are no less than 200 nucleotides and participate in the initiation and progression of various diseases, especially cancers ( Chen et al, 2020a ; Huang et al, 2021 ; Kotani et al, 2021 ; Luo et al, 2021 ; Teng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the biological role of lncRNA in regulating osteoclast differentiation in vitro and controlling bone resorption in vivo is less studied yet. Wang's group identified the functional motif a lncRNA Nron that could regulate ERα stability to prevent bone loss [29]. In the present study, we have identified the lncRNA DANCR a key factor for sesamin-mediated osteogenesis and osteoclastogenesis, as well as the regulator in osteoporosis pathogenesis.…”
Section: Discussionmentioning
confidence: 62%